Revision of the Afrotropical genus Zetheumenidion Bequaert (Hymenoptera: Vespidae: Eumeninae) - Selis, Marco (Zootaxa, 2024)
A taxonomic revision of the Afrotropical genus Zetheumenidion Bequaert, 1926 is presented. Four new species (Zetheumenidion abruptum sp. nov., Zetheumenidion concinnoide sp. nov., Zetheumenidion latum sp. nov. and Zetheumenidion minimum sp. nov.) are described; Zetheumenidion paeneplanum (Bequaert, 1926) stat. rev. is resurrected from synonymy with Z. pulchripenne (Cameron, 1910); Zetheumenidion femoratum flavissimum Giordani Soika, 1987 is raised to species level (Zetheumenidion flavissimum stat. nov.). A key to all known species is provided and the taxonomic placement of the genus is discussed.